Risk factors associated with the need for a tracheostomy in extremely low birth weight infants1. Issue 2 (29th May 2012) - Viswanathan, Sreekanth; Mathew, Ajith; Worth, Anne; Mhanna, Maroun J.
Abstract In an attempt to determine the risk factors associated with the need for a tracheostomy in extremely low birth weight (ELBW) infants, a retrospective, case control study was conducted (each infant with a tracheostomy [case] was matched to two controls). Medical records were reviewed for patients' characteristics, risk factors for tracheostomy and outcome. During the study period (June 1996 to Dec 2010), 934 ELBW infants were admitted to our institution and nine infants had a tracheostomy and were matched to 18 controls. There were no differences in birth weight (BW) and gestation age (GA) between cases and controls (828.1 ± 136.2 g vs. 822.0 ± 140.9 g [P = 0.91] and 26.6 ± 1.8 weeks vs. 26.5 ± 1.6 weeks [P = 0.88], respectively). In comparison to their controls, infants with a tracheostomy had a higher rate of intubation (median 13 [11–15] vs. 3 [2–5], P ≤ 0.001), a higher rate of total intubation attempts (median 18 [13–21] vs. 5.5 [3–7], P = 0.001), and more days of mechanical ventilation prior to their tracheostomy (mean 100.7 ± 27.7 vs. 29.2 ± 19.8 days [P < 0.001]). Also infants with a tracheostomy had a higher rate of non‐congenital upper airway obstruction (55% [5/9] vs. 0% [0/18]; P = 0.001), a higher rate of chronic lung disease (100% [9/9] vs. 5% [1/18]; P < 0.001) and a higher mortality (44% [4/9] vs. 0% [0/18]; P = 0.007) than their controls. In conclusion, chronic lung disease, multiple intubations and intubation attempts, duration of mechanical ventilation, and non‐congenital upper airway obstruction are risk factors associated with tracheostomies in ELBW infants. Pediatr Pulmonol. 2013; 48:146–150. © 2012 Wiley Periodicals, Inc.